Pharmacogenomic Regulation of the NF-kB–Nrf2 Axis by Curcumin: A Precision Molecular Approach to Inflammation and Oxidative Stress - Alisya, Questa Soundri; Khairunnisa; Abdullah (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2025)
Introduction: Chronic inflammation and oxidative stress are major mechanisms in degenerative diseases, including cancer, diabetes, and cardiovascular disorders. The NF-kB and Nrf2 pathways play a role in maintaining redox balance and inflammatory response. Curcumin, the main bioactive compound of Curcuma longa L., can simultaneously modulate both pathways through pharmacogenomic mechanisms influenced by individual genetic variations. Method: This study used the Systematic Literature Review method in accordance with the PRISMA 2020 guidelines. Searches were conducted in PubMed, Scopus, ScienceDirect, and Google Scholar until October 2025 using the keywords “Curcumin,” “NF-kB,” “Nrf2,” “Oxidative Stress,” and “Pharmacogenomics.” Studies assessing the molecular modulation of NF-kB/Nrf2 by curcumin and gene-dependent effects were included. Results and Discussion: A total of 31 studies met the inclusion criteria, including in vitro, in vivo, in silico, and clinical studies. Curcumin suppressed NF-kB activation and activated Nrf2/HO-1, thereby reducing ROS and proinflammatory cytokines. Variations in the ERCC5 rs751402 gene, as well as the expression of SLC7A11 and ATAD3A/B, influenced the cellular response to curcumin. In silico and network pharmacology analyses revealed multigenic targets related to inflammation and oxidative stress. Nanoformulations enhance bioavailability and clinical immune response. Conclusion: Curcumin acts as a dual-regulator pharmacogenomic agent that balances the NF-kB and Nrf2 pathways, reducing inflammation and oxidative stress in a gene-dependent manner. These findings support its potential as a natural biomolecule for the development of precision therapies for chronic diseases involving inflammation and oxidative stress.   Keywords: Curcumin, NF-kB, Nrf2, Oxidative Stress, Pharmacogenomics